Identification and evaluation of phenotypic characters and genetic diversity analysis of 1,558 foxtail millet germplasm resources for conservation and breeding - Xinwei Xue; Xinwei Xue; Zhikun Yu; Ankang Mu; Fan Yang; Dan Liu; Shi Zhang; Jialin Zhang; Yao Cheng; Yushan Zhao; Yongping Zhang; Xianrui Wang (Frontiers in Plant Science)
Foxtail millet (Setaria italica) is a specialty mixed grain crop that originated in China. This study comprehensively assessed the phenotypic variability of 1,558 foxtail millet accessions to explore their genetic diversity and facilitate effective germplasm conservation. A total of 25 traits, including 11 quantitative and 14 qualitative, were investigated based on the quantization of physical and chemical descriptors and digital image analysis. The findings revealed significant variations in the coefficient of variation (CV) among the quantitative traits, which ranged from 3.90–28.38%. That of the qualitative traits ranged from 7.44–66.20%. The Shannon-Wiener Index (H′) of the quantitative traits ranged between 1.86–2.08, and that of the qualitative traits ranged from 0.04–1.40. High genetic diversity was also detected among the 1,558 accessions. Based on hierarchical clustering, 1,558 accessions were separated into five categories. The principal component analysis (PCA) results indicated that 10 principal components were extracted when the cumulative contribution rate of the phenotypic traits reached 64.30%. The comprehensive evaluation F-values calculated based on correlation and PCA analyses of 25 phenotypic traits were applied to all the accessions, and the top 10 varieties were identified. Collectively, this study showed the rich genetic diversity of the 1,558 foxtail millet accessions, which could provide a baseline for breeding new millet varieties.